Gender Differences in Body Mass Index, Body Weight Perception, weight satisfaction, disordered eating and Weight control strategies among Indian Medical and Nursing Undergraduates - Vijayalakshmi, Poreddi; Thimmaiah, Rohini; Nikhil Reddy, S. Sai; B.V, Kathyayani; Gandhi, Sailaxmi; BadaMath, Suresh (Investigación y Educación en Enfermería, 2017)
Objective. To assess gender disparity in body weight perception, Body Mass Index (BMI), eight satisfaction and role of depression among undergraduate Medical and Nursing students. Methods. A descriptive cross sectional descriptive study was conducted in conveniently selected medical (n=241) and nursing (n=213) students of Bangalore, South India. Data was collected using self-administered SCOFF questionnaires. Results. Our findings revealed that men had a significantly higher BMI than women (t=5.403, p<0.001). More number of women compared to men, perceived themselves as ver weight (74.8%) and not satisfied with their weight status (81.6%). More men than women cored positively for disordered eating behaviors on SCOFF (45.4% vs. 31.1%) and EAT scale (16.5% vs. 8.7%). While, 48.2% of the women practice binge eating, 41.2% of the men practice it (p<0.004); more men (47.4%) than women (25.4%) exercised for more than sixty minutes (p<0.001) to control their weight. Conclusion.Findings indicate small differences between the genders that have to be taken in consideration in planning interventional programs to prevent eating disorders in this copulation. Descriptors: body mass index; weight perception; cross-sectional studies; students, nursing; students, medical; feeding and eating disorders. How to cite this article: Vijayalakshmi P, Thimmaiah R, Reddy SSN, Kathyayani BV, Gandhi S, Math SB. Gender Differences in Body Mass Index, Body Weight Perception, weight satisfaction, disordered eating and Weight control strategies among Indian Medical and Nursing Undergraduates. Invest. Educ. Enferm. 2017; 35(3):276-284.